MEMPOSISIKAN MANUSIA SEBAGAI TITIK SENTRAL DALAM BERHUKUM - M. Muslih M. Muslih (Jurnal LEX SPECIALIS, 2012)
Abstract Indonesia as a country that was once colonized by the Dutch in the period of time, then in the "state" a lot to absorb and adopt a "blue print" constitutional system of the colonial powers including how berhukumnya. As a country that joined in the Continental European countries are inherited how lawless Roman style adopts the Dutch legal positivism. Legal positivism is also internalized by both motherland (Indonesia), and have penetrated into the various elements of society, such as bureaucrats, prkatisi law and legal academics. However, there are also some "people" who have a point of view and arbitrate different ways (sociology of law) in which one of the initiators and driving is Satjipto Rahardjo, who in the service of the academia to develop a way that puts human arbitrate a central position in law. The law is no more a tool (instrument) therefore should not be legal kebaradaan shifts and even the "grind" of human existence and humanity. As a product of the law affiliated with "certainty" potentially huge move "track" of giving the public a tool for the protection of "the strong" against the weak. If this happens then the purpose of the law tend to stay away from the reality of the life of society, state and nation. Key Note :  Law and Human